2020
DOI: 10.1002/ps.6183
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Aedes aegypti nAChR gene family and molecular target of spinosad

Abstract: BACKGROUND Spinosad is an insecticide with unique mode of action (MOA) of disrupting nicotinic acetylcholine receptor and is efficacious against many insect species. Mutations in the nicotinic acetylcholine receptor (nAChR) α6 subunit have been identified that are associated with levels of spinosad resistance, but the molecular characterization of the nAChR gene family and a causative association between nAChR α6 and resistance to spinosad in Aedes aegypti, a primary vector of many arboviruses, have not yet be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 63 publications
(146 reference statements)
0
8
0
Order By: Relevance
“…The insecticide spinosad disrupts nicotinic acetylcholine receptors, which leads to paralysis, followed by death. The mechanism of resistance that has thus far been described is a mutation of the beta subunit of a gene coding for a nicotinic acetylcholine receptor [ 23 ]. It would be interesting to determine if the Phnom Penh population has a mutation within the same area of its genome, or to know if this phenotypic resistance is due to another selected mechanism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The insecticide spinosad disrupts nicotinic acetylcholine receptors, which leads to paralysis, followed by death. The mechanism of resistance that has thus far been described is a mutation of the beta subunit of a gene coding for a nicotinic acetylcholine receptor [ 23 ]. It would be interesting to determine if the Phnom Penh population has a mutation within the same area of its genome, or to know if this phenotypic resistance is due to another selected mechanism (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A splice variant of the gonadotropin-releasing hormone receptor AAEL011325 is downregulated in larvae exposed to brackish water compared to freshwater ( Durant et al 2021 ). Finally, the nicotinic acetylcholine receptor subunit gene Aaea6 (AAEL008055) is upregulated in response to posteclosion application of exogeneous juvenile hormone ( Zhu et al 2010 ) and has also been experimentally identified as the target of the insecticide spinosad ( Lan et al 2021 ); more generally, nAChR genes are known as the targets of neonicotinoid insecticides ( Casida 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The egg paper was placed in a feeding basin with added water and fodder. Larvae were reared in water with fish food, and the adults were kept at 26 °C, with relative humidity of 70% under a 16 h (light):8 h (dark) photoperiod, and were provided with an 8% sugar source [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, insecticide chemicals with new modes of action and activity against pest populations are required as alternatives. Small-molecule insecticides that destroy the targets of arthropod GPCRs have gradually become the focus of attention and may be used to develop next-generation insecticides [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%